Ambivalent Sexism Inventory among students from two universities at Arequipa - Fernández, Sandra (2017)
In this study we analyze the psychometric properties of Ambivalent Sexism Inventory, so then value its results after the application in a simple of 434 students from two universities at Arequipa City. The psychometric values indicate that the items are homogeneous and the test count with construct validity and reliability (α= 0.742). The results, also note significant differences between men and women, being the males who are more sexist than females, specially, in hostile sexism, benevolent paternalism sexism, and gender diff erentiation benevolent sexism. About the university, those students who come from public university are more sexism, so as those who study engineering.